The multidirectional impact of vitamin C on ageing processes and the health of the geriatric population - a literature review - Dubniański, Bartosz; Fudali, Kacper; Hejnowicz, Mateusz; Tymec, Jan; Wajerowska, Weronika; Nawracaj, Barbara; Browarny , Sonia (Quality in Sport, 2026)
Introduction The geriatric population is prone to micronutrient deficiencies, including vitamin C. It is found in plant food, and deficiencies can be treated with over-the-counter supplements. This work aims to expand knowledge about the beneficial effects of vitamin C on diseases in the elderly. Materials and Methods A thorough analysis has been conducted following PRISMA recommendations. The research data have been derived from scientific databases of Embase, PubMed, Cochrane Library and Google Scholar. Key word choice was based on their relevance to the review subject beforehand. The Stage of Knowledge Modern science has confirmed that vitamin C is essential for health. Through advanced technology, we clearly understand how it supports collagen synthesis, reduces oxidative stress, and helps maintain strong organs and blood vessels. These properties are important for keeping organs functioning properly as the body ages. However, modern medicine does not rely on biological theory alone. We now use Evidence-Based Medicine (EBM) to prove if a treatment works in real-world scenarios. Clinical trials are the most important tool we have because they separate theoretical benefits from proven results. Summary The wide range of effects of vitamin C, from supporting immunity and collagen synthesis to protecting the nervous system, is very important for maintaining the health of seniors. Thanks to its antioxidant properties, ascorbic acid delays the ageing process and supports cognitive function. Ensuring an adequate supply of this vitamin is an essential part of maintaining a good quality of life for the elderly. Regular intake of vitamin C should therefore be standard practice in the daily health care of seniors.